Rethinking domestic violence : the social work and probation response - Mullender, Audrey (London ; New York : Routledge, 1996)
Annotation This book explodes the myths concerning domestic violence and explores how the responses of social workers and probation officers to the people involved need to be far better coordinated and more effective.
Chapter Introduction -- chapter 1 The terms of the debate -- chapter 2 What do we know about domestic violence? -- chapter 3 Social work as part of the problem -- chapter 4 Developing good practice in social services departments -- chapter 5 Responses to domestic abuse in health and adult care settings -- chapter 6 The needs of children living with domestic abuse -- chapter 7 Social work and probation practice with families -- chapter 8 The probation service and domestic violence -- chapter 9 The men who abuse -- What kind of intervention in groups? -- chapter 10 Working together for change -- The wider context and the empowerment of women.
Includes bibliographical references (pages 280-301) and indexes.
Print version record.
eBooks on EBSCOhost
Keywords: Wife abuse -- Great Britain; Abused women -- Counseling of -- Great Britain; Abused wives -- Counseling of -- Great Britain; Social work with women -- Great Britain; Family violence -- Great Britain -- Prevention; Abusive men -- Counseling of -- Great Britain; Abusive men -- Rehabilitation -- Great Britain; Probation -- Great Britain; Domestic Violence; Spouse Abuse; United Kingdom; Femmes -- Violence envers -- Grande-Bretagne.; Femmes victimes de violence -- Counseling -- Grande-Bretagne.; Service social aux femmes -- Grande-Bretagne.; Probation (Droit) -- Grande-Bretagne.; Violence conjugale; FAMILY & RELATIONSHIPS -- Abuse -- Elder Abuse; FAMILY & RELATIONSHIPS -- Abuse -- Domestic Partner Abuse; Abused wives -- Counseling of; Abused women -- Counseling of; Abusive men -- Counseling of; Abusive men -- Rehabilitation; Family violence -- Prevention; Probation; Social work with women; Wife abuse; Great Britain